Trends of recycling management in Taiwan during 1999 – 2021 - Liao, Yen-Hsiung (SPC Journal of Environmental Sciences, 2023)
Purpose: Recycling is the process of converting waste materials into new materials and objects. It can prevent the waste useful materials and reduce the environmental pollution. Approach: Using rates of recycling materials information during 1999 – 2021. We approached the trend of resource and recycling management in Taiwan. Results: The years was significantly correlated with the recycling fund (r = 0.82, p<0.05) recycling rate of waste electronic and electric appliances (r = 0.92, p<0.05), waste containers (r = 0.88, p<0.05), waste lubricating oil (r = 0.87, p<0.05), waste information technology equipment (r = 0.73, p<0.05), waste dry cell batteries (r = 0.73, p<0.05), waste tires (r = 0.66, p<0.05), waste lead-acid batteries (r = 0.59, p<0.05), and waste lighting sources (r = 0.52, p<0.05) separately. Conclusion: The relations of raters of recycling materials and the years were higher than the relations of recycling materials and the recycling fund. This feedback system including participating people, cleaning teams, recycling enterprises, and the recycling fund has encouraged nationwide participation.